Development of Newly Formulated Nanoalumina-/Alkasite-Based Restorative Material - Reham M. Abdallah; Neven S. Aref (International Journal of Dentistry)
Purpose. Nanotechnology offers considerable scope in dentistry to improve dental treatment, care, and prevention of oral diseases through the use of nanosized biomaterials. This study assessed the effect of incorporating alumina nanoparticles (Al2O3 NPa) to the recently introduced alkasite-based restorative material (Cention N) on its mechanical properties and surface topographical features. Materials and Methods. Alumina nanopowder was incorporated into the powder component of Cention N at 5 and 10% (w/w). The unblended powder was used as a control. Compressive strength was assessed using a universal testing machine. Surface microhardness and roughness were evaluated using the Vickers microhardness test and surface profilometer, respectively. Surface topography was inspected using a scanning electron microscope (SEM). Data were analyzed by ANOVA and Tukey’s test (P<0.05). Results. Incorporation of either 5 or 10% (w/w) Al2O3 NPa into alkasite-based restorative materials (Cention N) increased both its compressive strength and surface microhardness. This increase was significant with the use of lower concentration Al2O3 NPa (5% w/w). Meanwhile, there was an increase in surface roughness values of Cention N modified with either 5 or 10% (w/w) Al2O3 NPa. This increase was only significant in the case of 10% (w/w) Al2O3 NPa. Conclusion. Incorporation of 5% (w/w) Al2O3 NPa into the newly introduced alkasite-based restorative material (Cention N) seems to produce a promising restorative material with high compressive strength and surface hardness without adversely affecting its surface roughness properties. Thus, nanotechnology implementation into Cention N restorative material may be strongly helpful for a diversity of clinical applications.